THE ROLE OF PUBLIC RELATIONS IN COMMUNICATION PSYCHOLOGY IN GOVERNMENT OF PROVINCIAL NORTH SUMATRA - Nurhanifah Nurhanifah (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
Communication is a basic thing for humans, since baby we are able to speak or expressing. Communication is an exchange of verbal and non-verbal language between the informant and the recipient of information in order to understand each other for a particular purpose. In this era of advanced and rising technology, every government and commercial institution must be able to keep up with the times, especially in improving the reputation and to broadcast the information. By maintaining good communication and image, the public can see the quality of performance and it affects the work programs implemented by the government. Therefore, this study aims to assess the public relations performance of the North Sumatra Provincial Government in conveying information to the public. This study uses qualitative research methods and through observation techniques. The results of this study indicate that in carrying out its role, the Public Relations of North Sumatra Province carries out two-way communication. Public Relations disseminates the policies and programs of the North Sumatra Provincial Government using communication channels in the form of mass media, both outdoor media in the form of billboards and posters, speeches and presentations, websites, special publications and digital catalogues as well as in connection with other mass media. Public Relations also made efforts to get a response from the public on the performance of the North Sumatra Provincial Government.